Changes in RSV-associated lower respiratory tract infections among hospitalized and outpatient children under 2 years in Northern Bavaria after general recommendation of Nirsevimab immunization in 2024 - Zhou, Ying; Hecker, Katharina; Engels, Géraldine; Andres, Oliver; Knies, Kerstin; Krempl, Christine; Weissbrich, Benedikt; Härtel, Christoph; Streng, Andrea; Liese, Johannes (Infection, 2025)
This study investigated changes in the incidence and age distribution of RSV-associated lower respiratory tract infections (RSV-LRTI) among children in Northern Bavaria after the general recommendation of Nirsevimab immunization in 2024. Postnatal Nirsevimab immunization coverage was assessed at the University Hospital Würzburg (UKW) in children born between 11/2024 and 03/2025. Age distribution of in- and outpatients < 2 years with PCR-confirmed RSV-LRTI was assessed from UKW (ICD-10 based) and pediatric practices in Würzburg for November-March in 2022/23 (S1), 2023/24 (S2) and 2024/25 (S3). Age distribution of RSV cases from nationwide mandatory laboratory RSV surveillance (Robert Koch-Institute) was analyzed for November-March in 2023/24 and 2024/25. Between 11/2024 and 03/2025, postnatal Nirsevimab immunization coverage for newborns at the UKW was 68% (566/833). In the RSV seasons S1/S2/S3, 98/84/29 children < 2 years with RSV-LRTI were hospitalized. The proportion of children < 1 year decreased from 78%/80% in S1/S2 to 42% in S3 (S1 vs. S3 p < 0.001, S2 vs. S3 p < 0.001). In 36/68/30 outpatients < 2 years with RSV-LRTI, the proportion of children < 1 year decreased from 44%/60% in S1/S2 to 33% in S3 (S1 vs. S3 p = 0.358; S2 vs. S3 p = 0.014). In nationwide laboratory RSV surveillance, 23,171/12,826 children < 2 years were reported in S2/S3, with a decrease in the proportion of children < 1 year from 65% in S2 to 47% in S3 (p < 0.001). We observed a clear decrease of RSV-LRTI in hospitalized and outpatient infants < 1 year of age in the first RSV season, suggesting a relevant impact following Nirsevimab recommendation in Germany.